(3efjI GddHjH aj TQM GdJgPjHs - (3YejO GdOjf YHO GdeWdH Hf eMeO Hf Ydj Hf GdCYQL (B((3GdCYQLi(B) (3GdMSjfj s
(3ChdgG (B:s
(3hHYO aEf Edi Yde CUhd Gdabg s
(3BNQgG (B:s
(3YHGQI Yf GdMb ef ai GdCUd hGdaQhY ef MJi dh GbJUQ Ydi CMO s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3abg GdePGgH GdCNQis